Finding the VOICE: organic carbon isotope chemostratigraphy of Late Jurassic – Early Cretaceous Arctic Canada. (20th October 2020) - Galloway, Jennifer M.; Vickers, Madeleine L.; Price, Gregory D.; Poulton, Terence; Grasby, Stephen E.; Hadlari, Thomas; Beauchamp, Benoit; Sulphur, Kyle
Abstract: A new carbon isotope record for two high-latitude sedimentary successions that span the Jurassic–Cretaceous boundary interval in the Sverdrup Basin of Arctic Canada is presented. This study, combined with other published Arctic data, shows a large negative isotopic excursion of organic carbon (δ 13 Corg ) of 4‰ (V-PDB) and to a minimum of −30.7‰ in the probable middle Volgian Stage. This is followed by a return to less negative values of c . −27‰. A smaller positive excursion in the Valanginian Stage of c . 2‰, reaching maximum values of −24.6‰, is related to the Weissert Event. The Volgian isotopic trends are consistent with other high-latitude records but do not appear in δ 13 Ccarb records of Tethyan Tithonian strata. In the absence of any obvious definitive cause for the depleted δ 13 Corg anomaly, we suggest several possible contributing factors. The Sverdrup Basin and other Arctic areas may have experienced compositional evolution away from open-marine δ 13 C values during the Volgian Age due to low global or large-scale regional sea levels, and later become effectively coupled to global oceans by Valanginian time when sea level rose. A geologically sudden increase in volcanism may have caused the large negative δ 13 Corg values seen in the Arctic Volgian records but the lack of precise geochronological age control for the Jurassic–Cretaceous boundary precludes direct comparison with potentially coincident events, such as the Shatsky Rise. This study offers improved correlation constraints and a refined C-isotope curve for the Boreal region throughout latest Jurassic and earliest Cretaceous time.